Determinants and value relevance of corporate tax planning / Rohaya Md Noor - Md Noor, Rohaya (2008)
The goal of this research is to provide evidence on the pervasiveness of tax planning activities among the publicly-listed Malaysian firms during the new tax regime 2000- 2004. The pervasiveness of these tax planning activities resulted from the provision of tax incentives and different rules in tax reporting and financial reporting which have a significant impact on corporate tax burdens, that is, corporate effective tax rates (ETRs). Using a micro backward-looking approach of a balanced panel data for 294 listed firms during the years 2000-2004, this study examines the impact of tax policy and dual reporting systems on corporate ETRs, the determinants of corporate ETRs, the variation of corporate ETRs from the statutory tax rate, the extent of gap between financial accounting income and taxable income (book-tax differences), and the value relevance of taxable income as an earnings quality indicator and performance measure.